Behavioural characteristics and financial distress - Yvonne McCarthy (European Central Bank (ECB), 2011)
Using a new nationally representative survey of financial capability and experience in the UK and Ireland, I investigate the key factors that cause individuals to experience financial distress. In this context, a key area that I focus on is whether individuals' behavioural traits, such as their capacities for self-control, planning, and patience, affect their ability to stay out of financial trouble. I find that the variables that proxy for these behavioural characteristics are both statistically significant and economically important for predicting both mild and extreme forms of financial distress, in a regression controlling for demographic and socio-economic factors. Furthermore, behavioural traits emerge as having a stronger impact on the incidence of financial distress than education or financial literacy. The results raise questions about whether policy can be oriented towards improving financial habits and mitigating the impact of behavioural characteristics on personal finances.
Keywords: C25; D14; 330; Behaviour; debt; financial literacy; Financial Strain; Personal Finance; Kapitalanlage; Privater Haushalt; Persönlichkeitspsychologie; Anlageverhalten; Finanzwissen; Schulden; Großbritannien; Irland